Targeted Phototherapy by Niobium Carbide for Mammalian Tumor Models Similar to Humans - Liu, Zhao; Jiang, Shan; Tian, Yuhang; Shang, Haitao; Chen, Kexin; Tan, Haoyan; Zhang, Lei; Jing, Hui; Cheng, Wen (Frontiers in Oncology, 2022)
Background In the past few decades, nanomaterial‐mediated phototherapy has gained significant attention as an alternative antitumor strategy. However, its antitumor success is majorly limited to the treatment of subcutaneous tumors in nude mice. In fact, no studies have been previously conducted in this area/field on clinically‐relevant big animal models. Therefore, there is an urgent need to conduct further investigation in a typical big animal model, which is more closely related to the human body. Results In this study, niobium carbide (NbC) was selected as a photoactive substance owing to the presence of outstanding near-infrared (NIR) absorption properties, which are responsible for the generation of NIR‐triggered hyperthermia and reactive oxygen species that contribute towards synergetic photothermal and photodynamic effect. Moreover, the present study utilized macrophages as bio‐carrier for the targeted delivery of NbC, wherein phagocytosis by macrophages retained the photothermal/photodynamic effect of NbC. Consequently, macrophage-loaded NbC ensured/allowed complete removal of solid tumors both in nude mice and big animal models involving rabbits. Meanwhile, two‐dimensional ultrasound, shave wave elastography (SWE), and contrast‐enhanced ultrasound (CEUS) were used to monitor physiological evolution in tumor in vivo post-treatment, which clearly revealed the occurrence of the photoablation process in tumor and provided a new strategy for the surveillance of tumor in big animal models. Conclusion Altogether, the use of a large animal model in this study presented higher clinical significance as compared to previous studies.